An analysis of circuit breaker capacity according to IEC 60909 and IEC 60059 standards at the PT Borneo Alumina Indonesia electrical system - Hakim, Agustino Al; Gianto, Rudy; Purwoharjono; Kurnianto, Rudi; Yusuf, Ismail (Edelweiss Applied Science and Technology, 2024)
At PT Borneo Alumina Indonesia (PT BAI), the D01 Power Distribution System uses circuit breakers (CB) with a current rating capacity of 1250A for both incoming and outgoing 10kV busbars. Replacing outgoing CBs with the same capacity during maintenance leads to unnecessary waste. This study was conducted to examine the appropriate CB capacity as a substitute for the old CBs in the outgoing 10 kV busbars for loads of 10 kV induction motors and transformers so that recommendations can be made to improve efficiency during maintenance on the D01 Power Distribution System. The Electronic Transient Analyzer Program (ETAP) 19.0.1 software was used to perform short circuit simulations based on IEC 60909 and load flow simulations, which were then adjusted to IEC 60059 and CB products from Siemens. The results show that we can replace the current Siemens CB, which has a rated breaking current specification of 31.5kA, with 25kA during the maintenance period. We can also replace the rated peak value of 80kA with 63kA, and the rated current of 1250A with 630A. Replacement of CB specifications does not change/modify the switchgear panel because the replacement CB matches the brand, dimensions, and size of the currently installed CB. These findings would also help increase efficiency during maintenance on the D01 Power Distribution System. The discussion includes limitations and recommendations for future research.